Evidence of genetic hybridization of the wild boar and the indigenous black pig in Northern Greece - Laliotis George P. (Biotechnology in Animal Husbandry, 2018)
In Greece both the black indigenous pig and the wild boar are considered as species of valuable genetic diversity while their products achieve a valuable market price. However, many crop damages are recorded, with farmers to claim that wild boar hybrids are responsible. On the other hand, black pig classification is based on phenotypic characteristics, which does not ensure breed's homogeneity in case of hybridization. Using the PCR-RFLP methodology, pig samples (n=135) from different rearing situations (feral boars, semi-extensive black pigs and extensive wild boars) were examined in order to identify whether or not hybridization exists. In the examined feral population of wild boar a 26% of hybrids was noted, while in the case of the extensive farming population of wild pigs a hybridization of 11.76% was observed. Interestingly, in both cases of the examined black pigs' populations, a mentionable hybridization with wild boar was observed, reflecting probably an implemented breeding practice or uncontrolled mating with wild boars. A pivotal level (5-7%) of inbreeding rate was also noted in the examined populations. The immediate removal of hybrids from all the examined populations should be achieved, in order to prevent and eliminate further introgression, genetic depression and loss of genetic diversity for both populations of wild boar and black pig. Finally, the applied methodology may be used by state authorities or certifying organizations to test, control or inspect farms rearing wild boar or black pig populations in order to record and eliminate hybridization events between them.